Comparative transcriptomic analysis of apple and peach fruits: insights into fruit type specification. (27th December 2021) - Li, Muzi; Galimba, Kelsey; Xiao, Yuwei; Dardick, Chris; Mount, Stephen M.; Callahan, Ann; Liu, Zhongchi
SUMMARY: Fruits represent key evolutionary innovations in angiosperms and exhibit diverse types adapted for seed dissemination. However, the mechanisms that underlie fruit type diversity are not understood. The Rosaceae family comprises many different fruit types, including 'pome' and 'drupe' fruits, and hence is an excellent family for investigating the genetic basis of fruit type specification. Using comparative transcriptomics, we investigated the molecular events that correlate with pome (apple) and drupe (peach) fleshy fruit development, focusing on the earliest stages of fruit initiation. We identified PI and TM6, MADS box genes whose expression negatively correlates with fruit flesh‐forming tissues irrespective of fruit type. In addition, the MADS box gene FBP9 is expressed in fruit‐forming tissues in both species, and was lost multiple times in the genomes of dry‐fruit‐forming eudicots including Arabidopsis. Network analysis reveals co‐expression between FBP9 and photosynthesis genes in both apple and peach, suggesting that FBP9 and photosynthesis may both promote fleshy fruit development. The large transcriptomic datasets at the earliest stages of pome and drupe fruit development provide rich resources for comparative studies, and the work provides important insights into fruit‐type specification. Significance Statement: Rose family of plants exhibit a diverse array of fruit types when fruit flesh develops from different floral parts. Through comparative transcriptomic analyses of carefully dissected and staged fruit tissues from apple (a pome) and peach (a drupe), candidate regulators of fleshy fruit identity are identified and a step‐wise specification of fruit type via MADS box genes and phytohormones is proposed.